Physician's drug handbook - Beers, Michael F. (Philadelphia : Lippincott Williams & Wilkins, 2005)
Pocket quick reference of current information on more than 1000 generic and 3000 trade name drugs, including 64 recently approved drugs. For physicians and residents. Arranged alphabetically by generic name and includes classification, dosage forms and strengths, indications, color photos, contraindications, and interactions.
Includes index.
Keywords: Drugs -- Handbooks, manuals, etc; Pharmaceutical Preparations -- handbooks; Therapeutic Equivalency -- handbooks; Pharmaceutical Preparations -- Handbooks